Job tasks, time allocation, and wages - Ralph Stinebrickner; Todd R. Stinebrickner; Paul Sullivan (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This paper studies wage determination using the first longitudinal dataset containing joblevel task information for individual workers. Novel quantitative task measures detail the amount of time spent performing People, Information, and Objects tasks at different skill levels. These measures suggest natural proxies for on-the-job human capital accumulation and provide new insights about wage determination. Current job tasks are quantitatively important, with high skilled tasks being paid double the rate of low skilled tasks. There is no evidence of learning-by-doing for low skilled tasks, but strong evidence for high skilled tasks. Current and past high skilled information tasks are particularly valuable.
Keywords: 330